HLA-DR4-restricted T-cell epitopes from the mycobacterial 60,000 MW heat shock protein (hsp 60) do not map to the sequence homology regions with the human hsp 60. - Mustafa, A S (1996)
The mycobacterial 60,000 MW heat shock protein (hsp 60) is a major antigen recognized by mycobacteria-reactive human CD4+ T cells with lymphokine profiles and effector functions consistent with protective immunity. In addition, the presence of a large number of T-cell epitopes presented by several HLA class II molecules makes this antigen relevant to subunit vaccine design. However, the results from animal models as well as human studies suggest that the mycobacterial hsp 60 may induce T-cell-mediated autoimmune conditions. In humans, the expression of HLA-DR4 represents a risk factor for some autoimmune diseases. These observations suggest that the epitopes from the mycobacterial hsp 60 presented to T cells in the context of HLA-DR4 could be relevant to autoimmunity. This is the first report on identification of HLA-DR4-restricted T-cell epitopes from the mycobacterial antigen hsp 60. In total, five epitopes recognized in the context of HLA-DR4 by the M. leprae hsp 60-reactive CD4+ T-cell clones from a subject immunized with M. leprae were defined by synthetic peptides. Two of the epitopes were M. leprae-specific (aa 343-355, aa 522-534), whereas three epitopes were common to M. leprae and M. tuberculosis (aa 331-345, aa 441-455, aa 501-515). However, all of these epitopes belong to the regions that are highly divergent between the mycobacterial hsp 60 and the homologous human hsp 60 sequence, suggesting that the T cells recognizing the mycobacterial hsp 60 in the context of HLA-DR4 may not necessarily induce autoreactivity.